Hubungan antara Indeks Massa Tubuh dan Lingkar Perut dengan Tekanan Darah pada Siswa SMA Kristen 2 Binsus Tomohon - Rindorindo, Winny G.; Sapulete, Ivonny M.; Pangkahila, Erwin A. (Medical Scope Journal, 2020)
Abstract: Adolescence is a vulnerable age group to nutrition imbalance disorders. One complication of high anthropometric level is increased blood pressure or hypertension. This study was aimed to determine the relationship between body mass index and waist size to blood pressure among senior high school students in Tomohon. This was an analytical observational study with a cross sectional design. Subjects were 307 students of SMA Kristen 2 Binsus Tomohon consisting of 139 males and 168 females. Measurement of weight, height, and waist circumference (WC) as well as calculation of body mass index (BMI) were performed on all subjects. The Kolmogorof-Smirnov test showed that the data were not distributed normally. The Spearman correlation test obtained a p-value of 0.000 (p<0.05) for the correlation between BMI and WC to blood pressure (systolic and diastolic blood pressures). In conclusion, there were significant relationships between BMI and blood pressure as well as between waist circumference and blood pressure.Keywords: body mass index, waist size, blood pressureÂ Abstrak: Usia remaja sangat rentan terhadap gangguan keseimbangan gizi. Salah satu komplikasi dari nilai antopometri yang tinggi ialah naiknya tekanan darah (hipertensi). Penelitian ini bertujuan untuk mengetahui hubungan antara indeks massa tubuh (IMT) dan lingkar pinggang (LP) dengan tekanan darah pada siswa SMA di Kota Tomohon. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Subyek penelitian ialah siswa SMA Kristen 2 Binsus Tomohon yang berjumlah 307 siswa terdiri dari 139 laki-laki dan 168 perempuan. Pengukuran berat badan, tinggi badan, lingkar pinggang dan penghitungan IMT dilakukan pada seluruh subyek penelitian. Hasil uji normalitas Kolmogorof-Smirnov memperlihatkan data tidak terdistribusi normal, dilanjutkan dengan metode nonparametric correlation menggunaakan uji Spearman yang mendapatkan nilai p=0,000 (p<0,05) untuk hubungan antara IMT dan LP dengan tekanan darah baik sistol maupun diastol. Simpulan penelitian ini ialah terdapat hubungan bermakna antara indeks massa tubuh dan lingkar pinggang dengan tekanan darah.Kata kunci: indeks massa tubuh, lingkar pinggang, tekanan darah